Anorectal atresias - Taibo, Walter (Cirugía del Uruguay, 1973)
A study of anorectal atresia as possible cause of intestinal obstruction in the newborn is presented. Its incidence and embryology are studied as well as the clinical picture of all its forms. s empJ-¡.asized the fact that intestinal obstruction i5 not present when there is sorne communication to the exterior due to the presence of vaginal or perineal fistulae. Radiology is most important in order to demonstrate the }YPe of the anomaly and helps planning its treatment. Operati\¡'e indication and different surgical approaches are. studied, depending on the experience obtaine in our country.